Thermoplastic 3D Printing—An Additive Manufacturing Method for Producing Dense Ceramics. Issue 1 (31st August 2014) - Scheithauer, Uwe; Schwarzer, Eric; Richter, Hans‐Jürgen; Moritz, Tassilo
<x xml:space="preserve">Abstract</x> In our new approach—thermoplastic 3D printing—a high‐filled ceramic suspension based on thermoplastic binder systems is used to produce dense ceramic components by additive manufacturing. Alumina (67 vol%) and zirconia (45 vol%) suspensions were prepared by ball milling at a temperature of about 100°C to adjust a low viscosity. After the preparation the suspension solidified at cooling. For the sintered samples (alumina at 1600°C, zirconia at 1500°C), a density of about 99% and higher was obtained. FESEM studies of the samples' cross section showed a homogenous microstructure and a very good bond between the single printed layers.